Plastic Flow Establishment in Tubes a Comparison of Pressure Gradient and Yield Stress Change Effects - Letelier-Sotomayor, M; Stockle-Henriquez, J; Siginer, D (American Society of Mechanical Engineers, 2013)
The transient flow that follows an instantaneous change of yield stress of a magnetorheological(MR) fluid in round tubes is analyzed by an exact analytical method. The time required to establish steady flow of MR fluids after a sudden yield stress change as well as for combinations of step-change in the pressure gradient and yield stress is determined. Copyright © 2013 by ASME.